2007
DOI: 10.1007/s00392-007-0559-z
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and occurrence of atrial fibrillation in long-term follow-up of common type atrial flutter ablation:

Abstract: The two mainly accepted and applied techniques for the ablation of common type atrial flutter show an excellent outcome under the aspect of ablation efficacy and quality of life in longterm follow-up. Three years after the ablation procedure the majority of patients consider the intervention beneficial. Despite the relatively high appearance of atrial fibrillation in the long-term follow-up this effect is still traceable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 19 publications
1
4
0
1
Order By: Relevance
“…The follow-up duration was among the longest ever reported in similar studies [13,15,17]. Our data confirm that atrial fibrillation occurrence after ablation of TFL is significantly higher in patients with both TFL and atrial fibrillation before ablation than in patients with isolated TFL [2,4,8,10,11,13,19].…”
Section: Main Findingssupporting
confidence: 92%
See 1 more Smart Citation
“…The follow-up duration was among the longest ever reported in similar studies [13,15,17]. Our data confirm that atrial fibrillation occurrence after ablation of TFL is significantly higher in patients with both TFL and atrial fibrillation before ablation than in patients with isolated TFL [2,4,8,10,11,13,19].…”
Section: Main Findingssupporting
confidence: 92%
“…Different values of atrial fibrillation incidence after TFL ablation have been reported by various authors, ranging from 8 to 82% [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], which may be explained by differences in the populations studied, mainly in terms of preablation history of atrial fibrillation and follow-up length. Although it has been established that a history of atrial fibrillation before TFL ablation is the most important risk factor for atrial fibrillation occurrence after ablation [2,4,8,10,11,13], a significant incidence of atrial fibrillation has been reported even after ablation of isolated TFL [15,16].…”
Section: Introductionmentioning
confidence: 98%
“…Study cohort: The number of patients lost in long term follow up is consistent with long-term surveys using written questionnaires 14, 19. A significant number of submitted questionnaires had to be excluded because they were not fully completed.…”
Section: Discussionmentioning
confidence: 86%
“…Finally, the questionnaire completion rate was excellent; all patients answered the questionnaire at baseline (prior to ablation procedure) and at follow-up. Therefore, there were neither blank questionnaires nor incomplete items, unlike other studies [ 13 , 24 , 25 ] in which the questionnaire was retrospectively completed, making it more difficult to complete and to evaluate the health status before and after a particular treatment.…”
Section: Discussionmentioning
confidence: 99%